Psychometric Evaluation of the Korean Version of the Student Evidence-Based Practice Questionnaire (S-EBPQ) - Jung Eun Park; Jee-In Hwang (Elsevier, 2021)
Purpose: Evidence-based practice (EBP) is a key competency that undergraduate nursing students need to learn, as EBP competence is essential for the effective implementation of EBP. However, few studies have comprehensively assessed the aspects of EBP competence using a reliable and valid measure specific to Korean nursing students. This study aimed to translate the Student Evidence-Based Practice Questionnaire (S-EBPQ) into Korean and evaluate its psychometric properties. Methods: The original S-EBPQ was translated into Korean. After a pilot test, a convenience sample of 249 college students with more than four weeks of clinical training experience was selected from three universities in September 2017. Reliability and construct validity were evaluated using exploratory and confirmatory factor analyses. Concurrent validity was evaluated by correlating the measure with informatics competency. Results: The exploratory factor analysis revealed four factors that explained 66.3 of the variance. The confirmatory factor analysis yielded a 4-factor structure (χ2/df = 1.52, p < .001, standardized root-mean-square residual = .07, root-mean-square error of approximation = .07, goodness of fit index = .84, comparative fit index = .91). The Cronbach's α was .81 for the total scale. The scale's correlation with informatics competency was r = .55. Conclusions: The Korean S-EBPQ is a reliable and valid tool that has utility for assessing EBP competence in Korean nursing students and for making comparisons of the EBP competence of nursing students from other countries.